2018
DOI: 10.1007/s10456-018-9658-x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-22 promotes tumor angiogenesis

Abstract: T H 17 cells play important yet complex roles in cancer development and progression. We previously reported that T H 17 cells and IL-17 mediate resistance to anti-VEGF therapy by inducing recruitment of immunosuppressive and proangiogenic myeloid cells to the tumor microenvironment. Here, we demonstrate that IL-22, a key effector cytokine expressed by T H 17 cells, directly acts on endothelial cells to promote tumor angiogenesis. IL-22 induces endothelial cell proliferation, survival, and chemotaxis in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 43 publications
(54 reference statements)
1
51
0
1
Order By: Relevance
“…The classic 'Th-17-like' inflammatory response to damaged epithelial junctions in tumor cells exacerbates tumor growth and progression (43). IL-22 and IL-32 are important agents in the 'Th-17 like' inflammatory response and have recently been demonstrated to be closely associated with tumor angiogenesis (44,45). Collectively, these findings reveal a complex relationship between cancer-associated inflammation, tumorigenesis and tumor progression, which are mutually causal and reinforcing.…”
Section: Discussionmentioning
confidence: 99%
“…The classic 'Th-17-like' inflammatory response to damaged epithelial junctions in tumor cells exacerbates tumor growth and progression (43). IL-22 and IL-32 are important agents in the 'Th-17 like' inflammatory response and have recently been demonstrated to be closely associated with tumor angiogenesis (44,45). Collectively, these findings reveal a complex relationship between cancer-associated inflammation, tumorigenesis and tumor progression, which are mutually causal and reinforcing.…”
Section: Discussionmentioning
confidence: 99%
“…This was further supported by our data which showed decreased inflammation (no TNFα staining) in the histological sections of the EFP containing our cryogel‐0.25 wt%CPO bioscaffolds. When we compared the EFP from animals which received cryogel‐0.25 wt%CPO bioscaffolds to those which had cryogel alone bioscaffolds, there was a significant increase in the expression of IL‐2259 (i.e., a cytokine which promotes angiogenesis), LIF60 (i.e., a cytokine which regulates microvessel density), and a significant decrease in expression of IL28,61 IL‐17α,62 and TNF‐α58 (i.e., proinflammatory cytokines). However, the decreased efficiency of islet transplantation in our control experiments (i.e., islets alone transplanted into the EFP) compared to previous studies50,63,64 can be attributed to i) the use of 500 islets with islet diameters in the range of 50–150 µm—this is less than 500 islet equivalents or islet equivalent (IEQ) used in previous studies50,63,64 (one IEQ is considered equivalent to an islet with a diameter of 150 µm) and ii) our animals exhibited a higher initial blood glucose at the day of transplantation (i.e., 538 ± 25 mg dL −1 ) when compared to the above mentioned studies (i.e., 250 or 350 or 500 mg dL −1 )50,63,64—this would mean that our animals had a greater degree of dysglycemia and hence are much more dependent on the success of their islet transplant.…”
Section: Discussionmentioning
confidence: 99%
“…After the functional enrichment analysis, we found that some enriched biological processes were reported to be associated with tumor progression. For example, i) cell adhesion was usually reported to show a reduced number of tumor cells since 1962 (Holmberg 1962); ii) autophagic cell death occurs via the activation of autophagy, which has been reported to play roles in tumor suppression (Mathew et al 2009); iii) the positive regulation of cell proliferation is a common characteristic of cancer, and the inhibition of cancer cell proliferation may serve as a potential target for cancer treatment (He et al 2018); iv) changes in extracellular matrix organization were reported with crucial roles in cancer metastasis (Goreczny et al 2017;Sada et al 2016); v) positive regulation of blood coagulation was frequently reported in cancer progression (Tikhomirova et al 2016); and vi) angiogenesis is still considered a common characteristic of tumorigenesis in many studies (Baltrunaite et al 2017;Protopsaltis et al 2019;Ziegler et al 2016).…”
Section: Discussionmentioning
confidence: 99%